Introduction to Statistical Quality Control - Montgomery, Douglas C. (John Wiley & Sons, 2009)
This book is about the use of modern statistical methods for quality control and improvement. The objective is to give the reader a sound understanding of the principles and the basis for applying them in a variety of situations.